Variation in early growth in a second-generation whitewood (Endospermum medullosum) progeny trial in Vanuatu. Issue 3 (17th May 2017) - Page, T.; Bush, D.; Sethy, M.; Doran, J.
ABSTRACT: Endospermum medullosum (whitewood) is a commercially important plantation and agroforestry timber species in Vanuatu, used locally and for export. Commercial development depends on both increased productivity and genetic resource conservation. A second-generation progeny trial on Espiritu Santo Island was measured at ages 2 and 3 years. Growth traits were of low-to-moderate heritability, varying from 0.13 for height at 2 years, to 0.30 for diameter at breast height (DBH) at 3 years. Genetic correlations between growth and form traits were generally encouraging, with form at 3 years moderately-positively correlated (0.49 to 0.56) with the growth measures at ages 2 and 3 years, and no adverse correlations evident. Families of Espiritu Santo origins were consistently amongst the highest ranked for both growth and form traits, while families of Malekula and Pentecost Island performed poorly. These results are supportive of the recurrent selection and breeding strategy being implemented to deliver economic gains in growth traits. With natural populations severely depleted or extinct, the breeding population constitutes a repository for genetic variation already lost from wild sources. The long-term sustainability of the breeding program will therefore depend on provisions made for both improvement (narrowing of variation) and conservation (broadening of variation) of genetic resources.